Conceptualising dignity in the context of social security: Bottom‐up and top‐down perspectives. (13th August 2019) - Patrick, Ruth; Simpson, Mark
Abstract: Dignity and social security have been closely associated since at least the Universal Declaration of Human Rights in 1948, but there is a lack of clarity around what dignity means in this context. This article explores how two key stakeholders—out‐of‐work benefit recipients and policymakers—understand dignity in the context of social security, drawing on qualitative research with each group. The evidence presented notes a relative absence of direct references to dignity among policymakers, although related issues are nonetheless discussed, whereas benefit recipients commonly articulate experiences of undignified treatment and the negative impact this has on their lives. This article's exploration of dignity is of particular relevance to Scotland, where recent framework legislation includes the principle that their security system should be underpinned by "respect for the dignity of individuals." The authors propose that a social security system that protects dignity must take account of distributional, relational, and intrinsic aspects of dignity—providing sufficient income, treating users with respect, and avoiding interventions or discourses that are disrespectful and dehumanizing. Further, the authors question whether it is possible for dignity to enjoy meaningful protection within highly disciplinary conditional welfare regimes.